Media Pembelajaran Seni Budaya Berbasis Flipping Book - Sonhaji Arif (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2017)
The learning media should ideally be able to give readers the opportunity to build their own knowledge. Some research results show that (single media and multimedia) has contributed significantly. Special media in multimedia format has played an important role in the world of education. The use of multimedia that uses attractive visualization can help students understanding, as well as provide convenience in teaching and learning activities, which in turn can provide solutions to educational problems. The development model used is the 4D model (Thiagarajan et al, 1974). Media validation includes 2 media experts and 2 material experts. Product trials include individual trials, small groups. The result of media development of